The instability characteristics of amorphous silicon thin film transistors with various interfacial and bulk defect states - Cheng, HC; Tsai, JW; Huang, CY; Luo, FC; Tuan, HC (My University, 1997)
The instability characteristics of hydrogenated amorphous silicon (a-Si:H) thin film transistors (TFTs) with various interfacial and bulk defect states were systematically investigated. It was found that, under positive bias stresses; the threshold voltage shifts of a-Si:H TFT's with the same interfacial defect states but with different bulk defect states exhibited similar threshold voltage shift characteristics. In contrast, a-Si:H TFTs with different interfacial defect states but the same bulk defect states showed threshold voltage shifts proportional to the interfacial defect states under positive bias stresses. Furthermore, both the above kinds of a-Si:H TFT under positive bias stresses exhibited that the subthreshold swing shift characteristics closely related to both the interfacial and bulk defect states.
Keywords: amorphous silicon; thin film transistor; bias stress; threshold voltage shift; subthreshold swing shift